PHARMACOGNOSTICAL, ANALYTICAL STUDY AND HPTLC EVALUATION OF SHAMPAKADI KWATHA, A POLYHERBAL FORMULATION FOR PHARMACEUTICAL STANDARDIZATION - Rao, Rajdip; Thakar, Anup; CR, Harisha; Shukla, V.J. (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Shampakadi kwatha is mentioned in Ayurvedic classics as a therapeutic formulation of Basti to treat Musculo-skeletal diseases like Katishool (Lumbar spondylosis). Back pain is the most common ailment in today’s busy life. Majority of us have experienced one or more episodes of back pain in our lives and many of us live with chronic symptoms. Incidences of low back pain affects 60-85% in adults and lumbar Spondylosis is responsible for about 10% of all back pain. Shampakadi kwatha contains Aragvadha (Cassia fistula Linn.), Eranda (Ricinus communis.Linn), Punarnava (Boerhavi diffusa Linn) etc. which have Shoolaghna and Vatahara property. Method: Shampakadi kwatha powder was evaluated for their pharmacognostic and pharmaceutical analysis. Results: Microscopic characters were found of all the contents of Shampakadi kwatha. Results obtained in pharmaceutical parameters of Shampakadi kwatha powder like loss on drying 12.18%, Ash value 9.06%, Alcohol soluble extract 62.15% w/v etc. HPTLC profile of Shampakadi kwatha powder showed similarities in number of spots. Conclusion: From the study, data developed can be espoused for laying down the standards for Shampakadi kwatha. Keywords: HPTLC, Pharmacognostical, Pharmaceutical analysis, Shampakadi Kwatha